SISTEM KEAMANAN LEMARI PENYIMPANAN BARANG MENGGUNAKAN PASSWORD SEBAGAI KENDALI AKSES DAN SENSOR ULTRASONIK SEBAGAI PENDETEKSI BARANG - Muhammad Akbar; Robby Candra; Yuli Karyanti; Yulia Chalri; Hasma Rasjid (Universitas Gunadarma, 2024)
A sense of security in storing items and ease of finding storage cabinets in public places such as shopping centers is absolutely necessary, but this may still not be fulfilled because storage cabinets still use conventional locks or still use cards to store items, plus it requires a time-consuming process to look for an empty storage cabinets. Therefore, the creation of a storage cabinets model in this research aims to implement a security system for a storage cabinets with access control using a password and to know whether there are items in the storage cabinets or not so that users can find out which storage cabinets are available/empty. This storage cabinets security device uses a solenoid as a lock, a servo motor to actuate the cabinets door, an ultrasonic sensor to detect items in the cabinets and control it via keypad and LCD to display the condition of the cabinets use. This tool uses an Arduino Mega microcontroller as the main controller and password storage medium, thereby producing output automatically where the solenoid will open/close and the servo motor moves to open/close the cabinets door. The tool can function to detect items in cabinets and based on item detection using an ultrasonic sensor the user can find out which cabinets are empty and the cabinets door will open based on a password determined by each user to ensure the security of the items stored.